TRANSFORMATIONAL LEADERSHIP MANAGEMENT MI LUTHFUL ULUM IN ACHIEVING AN EXCELLENT MADRASAH - Kunarso, Kunarso; Islah, Islah; Sujito, Sujito (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
MI Luthful Ulum's Transformational Leadership Management in Achieving Excellent Madrasa in Pati Regency. MI Luthful Ulum's Transformational Leadership Management in Achieving Superior Madrasas in Pati Regency is as follows: 1) the principal's transformational leadership can be interpreted as the form or style applied by the principal in influencing his subordinates (teachers, administrative staff, and all employees) to achieve performance and desired educational goals. 2) The main principle of transformational leaders is that they have high competence and vision to realize success, leaders can inspire subordinates to respond with great enthusiasm and commitment to achieving goals. 3) Transformational leadership will have a positive influence on the relationship between superiors and subordinates in Islamic education. With the concept of transformational leadership, subordinates will feel trust, admiration, pride, loyalty and respect for their superiors and will be motivated to do work with results that exceed the targets that have been determined together.  These positive changes such as setting an example, such as leaders showing professional behavior in the teaching and learning process, honesty, discipline (on time), ability to collaborate and relationships between students and teachers will influence teachers at Islamic Education Institutions. 4) Implementation of MI Luthful Ulum's transformational leadership management in achieving superior madrasas in the District. Pati in the picture above there are 4 descriptions of transformational leadership, such as leaders who pay attention to the needs of subordinates, leaders who raise issues of need to a higher level, leaders who listen to subordinates' problems at work, and leaders who build subordinates' self-confidence.